Design, build and test of ejector based multi-evaporator refrigeration system - Hu, Yu (2016)
This thesis proposed a novel ejector based multi-evaporator refrigeration system (MERS). The energy inefficiency of conventional multi-evaporator refrigeration system was analyzed and this novel ejector based multi-evaporator refrigeration system was introduced. The working principle is described in detail and the possible advantage and disadvantage is discussed. The experimental platform is built to conduct the comparison study between conventional MERS and ejector based MERS. The system is introduced from architecture to detailed functional programming. Experiments have been done on the experimental platform to compare the energy consumption of these two systems. By analyzing the performance of the novel ejector based multi-evaporator refrigeration system, several improvements and future works are proposed.